Perspectives on geologic carbon storage - Albertz, Markus; Stewart, Simon A.; Goteti, Rajesh (Frontiers in Energy Research, 2023)
Geologic carbon storage is a fundamental pillar of carbon management that helps mitigate greenhouse gas emissions and addresses the negative effects of address climate change. Viable CO2 storage sites share some of the same elements required for successful petroleum systems. For example, while reservoir, seal, and trap are required, migration pathway and timing are not important for CO2 storage, because rather than withdrawing fluid from a trap, CO2 storage involves injection into a geologic trap. Conceptually, this represents a form of reverse production. Numerous petroleum traps around the world, as well as naturally occurring CO2-producing fields and natural gas storage sites attest that safe, long-term storage is possible. Research over the past two decades identified five methods of Geologic Carbon Storage which have been validated through several demonstration and pilot projects around the world: (1) storage in depleted oil and gas fields, (2) use of CO2 in enhanced oil recovery (EOR), (3) storage in saline formations / aquifers, (4) injection into deep unmineable coal seams, and (5) in-situ / ex-situ carbon mineralization. The greatest volumetric potential for GCS is found in saline aquifers which are present throughout the world’s sedimentary basins.